Discoursal aspects of interlanguage in the argumentative essays of UiTM Sarawak Diploma Students / Affiana Kadri … [et.al.]. - Kadri, Affiana; Potley@Faizal Hakim, Simon Phillip@Faizal Hakim (2015)
This project aims to investigate the English Language errors produced by undergraduate students preparing for the Malaysian University English Test (MUET) in a large Malaysian public university. Errors are seen as one of the ways in which the Interlanguage of language learners can be understood. The Interlanguage refers to the incomplete knowledge of grammar structures and the strategies used to learn them which are characteristic of language learners at particular stages of their learning process. This project will collect a mini-corpus of argumentative essays written by BEL 260 students at the UiTM Sarawak Samarahan Campus. BEL 260 is a course designed to prepare students at Diploma level for their Malaysian University English Test. A corpus is a text database containing language examples collected from real-life writers and speakers.